The Effect of Problem Based Learning Model toward the Ability of Science Literacy in 3rd Grade Students - Uswatun Hasanah; Prima Mutia Sari (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze how much influence the use of a problem-based learning model on the ability of science literacy learners in Learning Natural Sciences class III Makassar State Elementary School. This study uses the experimental method, and the form of research is a quasi-experiment. With the design of posttest only control design, and sampling techniques using purposive sampling. Based on the results of data analysis, the average post-test in the experimental class was 33.82 while in the control class was 23.18. Hypothesis test results using T-test with Mann Withney formula, obtained by Asymp. Sig (2-tailed) 0.014. The value of asymptotic significance in the calculation of the t-test is smaller than the significance level of 0.05, thus the HA is accepted, so that from the test results there is a significant influence between the results of scientific literacy students who use problem-based learning model.